Prediksi Angka Pengangguran Menggunakan Regresi Linear Berdasarkan Indikator Pendidikan dan Pertumbuhan Ekonomi di Jawa Tengah - Naurah Qolbia Salamah; Khoirunisa, Rindy Nabila; Ummu, Azzatul; Nur Afisa, Anita Rachma; Hamidah, Hilda Zahra (Lembaga Bale Literasi, 2025)
This study aims to predict the unemployment rate in Central Java Province using a linear regression method based on indicators of education level and economic growth. Secondary data from 2024, collected from various regencies and cities in Central Java, were analyzed to examine the relationship between the independent variables—education level and economic growth—and the dependent variable, unemployment rate. The analysis results show that an increase in the average years of schooling significantly reduces the unemployment rate, while economic growth also contributes to lowering unemployment, although its effect is smaller and varies across regions. The developed linear regression model is able to explain most of the variation in the unemployment rate and is used to project unemployment trends up to 2027, with a predicted decline in unemployment, assuming continued improvement in education quality and stable economic growth. These findings emphasize the importance of synergy between enhancing education quality and inclusive economic growth as key strategies to reduce unemployment in Central Java. However, unemployment is a complex issue influenced by other factors such as infrastructure, regional policies, and workforce readiness, thus requiring a comprehensive approach. This study is expected to provide a foundation for formulating more targeted policies to alleviate unemployment in the region.